Study Of Nitellahyalina (Charales) Based On Oospore Wall Ornamentation - Naz, Sabrina; Moniruzzaman, Md; Diba, Nasrin Jahan; Chowdhury, Arfatun Nahar; Azam, Shah Md Golam Gousul (Bangladesh Journal of Plant Taxonomy, 2023)
Abstract not available. Bangladesh J. Plant Taxon. 30(2): 283-286, 2023 (December)